Formulas and Flexibility in Trade Negotiations : Sensitive Agricultural Products in the World Trade Organization's Doha Agenda - Jean, Sébastien; Laborde, David; Martin, Will (World Bank, 2013)
Many trade negotiations involve large cuts in high tariffs, while allowing smaller cuts for an agreed share of politically sensitive products. The effects of these flexibilities on market access opportunities are difficult to predict, creating particular problems for developing countries in assessing whether to support a proposed trade agreement. Some widely used ad hoc approaches for identifying likely sensitive products—such as the highest-bound-tariff rule—suggest that the impact of a limited number of such exceptions on average tariffs and market access is likely to be minor. Applying a rigorous specification based on the apparent objectives of policymakers in setting the prenegotiation tariff enables more accurate assessment of the implications of sensitive-product provisions for average agricultural tariffs, economic welfare, and market access under the Doha negotiations. The analysis concludes that highest-tariff rules are likely to seriously underestimate the impacts on average tariffs and that treating even 2 percent of tariff lines as sensitive is likely to have a sharply adverse impact on economic welfare. The impacts on market access are also adverse, but much smaller, perhaps reflecting the mercantilist focus of the negotiating process.